Acute Kidney Injury in Pediatric Inflammatory Multisystem Syndrome Temporally Associated With Severe Acute Respiratory Syndrome Coronavirus-2 Pandemic: Experience From PICUs Across United Kingdom*. Issue 12 (December 2020) - Deep, Akash; Upadhyay, Gaurang; du Pré, Pascale; Lillie, Jon; Pan, Daniel; Mudalige, Nadeesha; Kanthimathinathan, Hari Krishnan; Johnson, Mae; Riphagen, Shelley; Dwarakanathan, Buvana; Raffaj, Dusan; Sundararajan, Santosh; et al.
Abstract : Objectives: To study the prevalence, evolution, and clinical factors associated with acute kidney injury in children admitted to PICUs with pediatric inflammatory multisystem syndrome temporally associated with severe acute respiratory syndrome coronavirus-2. Design: Multicenter observational study. Setting: Fifteen PICUs across the United Kingdom. Patients: Patients admitted to United Kingdom PICUs with pediatric inflammatory multisystem syndrome temporally associated with severe acute respiratory syndrome coronavirus-2 between March 14, 2020, and May 20, 2020. Interventions: None. Measurements and Main Results: Deidentified data collected as part of routine clinical care were analyzed. All children were diagnosed and staged for acute kidney injury based on the level of serum creatinine above the upper limit of reference interval values according to published guidance. Severe acute kidney injury was defined as stage 2/3 acute kidney injury. Uni- and multivariable analyses were performed to study the association between demographic data, clinical features, markers of inflammation and cardiac injury, and severe acute kidney injury. Over the study period, 116 patients with pediatric inflammatory multisystem syndrome temporally associated with severe acute respiratory syndrome coronavirus-2 were admitted to 15 United Kingdom PICUs. Any-stage acute kidney injury occurred in 48 of 116 patients (41.4%) and severe acute kidney injury in 32 of 116 (27.6%) patients, which was mostly evident at admission (24/32, 75%). In univariable analysis, body mass index, hyperferritinemia, high C-reactive protein, Pediatric Index of Mortality 3 score, vasoactive medication, and invasive mechanical ventilation were associated with severe acute kidney injury. In multivariable logistic regression, hyperferritinemia was associated with severe acute kidney injury (compared with nonsevere acute kidney injury; adjusted odds ratio 1.04; 95% CI, 1.01–1.08; p = 0.04). Severe acute kidney injury was associated with longer PICU stay (median 5 days [interquartile range, 4–7 d] vs 3 days [interquartile range, 1.5–5 d]; p < 0.001) and increased duration of invasive mechanical ventilation (median 4 days [interquartile range, 2–6 d] vs 2 days [interquartile range, 1–3 d]; p = 0.04). Conclusions: Severe acute kidney injury occurred in just over a quarter of children admitted to United Kingdom PICUs with pediatric inflammatory multisystem syndrome temporally associated with severe acute respiratory syndrome coronavirus-2. Hyperferritinemia was significantly associated with severe acute kidney injury. Severe acute kidney injury was associated with increased duration of stay and ventilation. Although short-term outcomes for acute kidney injury in pediatric inflammatory multisystem syndrome temporally associated with severe acute respiratory syndrome coronavirus-2 appear good, long-term outcomes are unknown. Abstract : Supplemental Digital Content is available in the text.